A multi‐port, narrow‐wide band achievable, reconfigurable antenna for cognitive radios. Issue 8 (12th May 2022) - C. Cleetus, Ros Marie; Bala Gnanadhas, Josemin
Abstract: This paper aims to propose a 4‐port integrated antenna system that is capable of exhibiting ultra wideband (UWB) and narrowband (NB) characteristics using excitation switching reconfiguration. In line with the requirements of the Cognitive Radio (CR), the UWB functionality makes the antenna capable of spectrum sensing and the NB feasibility allows the antenna to communicate with the spectrum. The proposed antenna is having a compact dimension of 40 mm × 35 mm × 1.6 mm and is printed on FR4 substrate with relative permittivity of 4.4. The antenna performance is analyzed as 3 scenarios. In all three, the antenna is found to cover the entire UWB spectrum approved by the federal communications commission (FCC), from 3.1 to 10.6 GHz. In addition to the UWB characteristics, each scenario provides at least one NB characteristic. In Scenario 1, the NB antenna 1 provides coverage from 6.87 to 8.67 GHz whereas, in Scenario 2, the NB antenna 2 provides dual‐band coverage from 2.99 to 4.27 GHz and 8.47 to 11.40 GHz. In Scenario 3, the NB antenna 3 operates in a single band from 4.09 to 7.09 GHz. Isolation between the antennas is found to be less than −15.9 dB in all the Scenarios. The lumped equivalent models of NB antennas are simulated and optimized in Applied Wave Research (AWR) software to match the antenna S‐parameters at their resonance frequencies. The simulated and measured results are in good agreement. The comparative analysis of the antenna with the previous works in the same area is also included in this paper.